2020
DOI: 10.1186/s12920-020-00836-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential alternative splicing between hepatocellular carcinoma with normal and elevated serum alpha-fetoprotein

Abstract: Background Serum alpha-fetoprotein (AFP) is the approved serum marker for hepatocellular carcinoma (HCC) screening. However, not all HCC patients show high (≥ 20 ng/mL) serum AFP, and the molecular mechanisms of HCCs with normal (< 20 ng/mL) serum AFP remain to be elucidated. Therefore, we aimed to identify biological features of HCCs with normal serum AFP by investigating differential alternative splicing (AS) between HCCs with normal and high serum AFP. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…FAM20A is associated with poor survival of HCC. Further experimental investigation on FAM20A should be performed to evaluate its potential as a diagnostic biomarker for the early diagnosis of HCC in a high-risk population ( 82 ). Interestingly, FN1 was co-screened with FAM20A in the above two articles, and FN1 was also found to act as a substrate of FAM20C and is essential in the development of glioma ( 18 ).…”
Section: The Role Of the Secretory Pathway Kinases Or Kinase-like Pro...mentioning
confidence: 99%
“…FAM20A is associated with poor survival of HCC. Further experimental investigation on FAM20A should be performed to evaluate its potential as a diagnostic biomarker for the early diagnosis of HCC in a high-risk population ( 82 ). Interestingly, FN1 was co-screened with FAM20A in the above two articles, and FN1 was also found to act as a substrate of FAM20C and is essential in the development of glioma ( 18 ).…”
Section: The Role Of the Secretory Pathway Kinases Or Kinase-like Pro...mentioning
confidence: 99%
“…In the study of "Differential alternative splicing (AS) between hepatocellular carcinoma with normal and elevated serum alpha-fetoprotein", Jin et al [5] reported an investigation of differential AS events in hepatocellular carcinoma (HCC) patients with high and normal serum alpha-fetoprotein (AFP) levels. Using RNA-seq data extracted from TCGA, they identified a set of AS events for genes that are enriched for cell migration or proliferation, and some of these genes are associated with gender and vascular invasion.…”
Section: Summaries Of Manuscripts In This Issuementioning
confidence: 99%